INTEGRASI NILAI-NILAI MODERASI BERAGAMA DALAM KURIKULUM SATUAN PENDIDIKAN DI SEKOLAH KATOLIK - Anastasia Bita; Yohana Sesa Ruing; Apriliana Buaq; Selly Dian Fratama; Yohana Cantika Bao Mbulu (Bahasa Indonesia, 2026)
This study aims to analyze the integration of religious moderation values within the educational curriculum of SMK catholic 2 WR. Soepratman Samarinda as an effort to develop tolerant, faithful, and patriotic students in a plural society. The increasing complexity of religious diversity in Indonesian highlights the importance of schools, especially catholic educational institutions, in shaping a culture of peace and respect for differences. To respond to this need, this research employed the literature review method by examining scientific articles, educational policies, church documents, and relevant academic discussion published between 2018 and 2025. The findings reveal that key values of religious moderation such as tolerance, justice, love, balance, and respect for diversity have been effectively integrate into the curriculum, spiritual formation, and charter-building programs. Teachers and school leaders serve as agents of moderation by fostering a culture of compassion and openness through exemplary conduct, interfaith dialogue, contextual learning, and collaborative social activities. Furthermore, the school has adopted the Merdeka curriculum in 2025.